Pengaruh Etika Kerja dan Etos Kerja Terhadap Integritas Kerja Karyawan PT. Golgon Medan - Purba, Alice Paulina (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2025)
In this modern era, every large company always has quality human resources. The implementation of a good work ethic as well as a directed work ethic will improve the work integrity of employees who will advance the company to be able to compete with other competing companies. The purpose of this study was to determine the effect of work ethics and work ethic on the work integrity of employees of PT. Golgon Medan. The research method used is a quantitative analysis method. The data used are primary and secondary data. The study population was 50 people using saturated sampling techniques where all members of the population were sampled. Variables are measured with a Likert scale. The data analysis technique used is multiple linear regression. Based on simultaneous analysis of work ethics and work ethic affect the work integrity of employees of PT. PT. Golgon Medan. Partially, there is an influence of work ethic variables on work integrity and there is an influence of work ethic on the work integrity of employees of PT. Golgon Medan.